IMPLEMETASI MEDIA PEMBELAJARAN CROSSWORD PUZZLE MENGGUNAKAN WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS - Samudra Pangestu, Agung; Ruja, I Nyoman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve student learning outcomes in Social Studies by implementing Crossword Puzzle learning media using the Wordwall platform. The method used is Classroom Action Research with two cycles implemented in class VIII of SMP Negeri 14 Malang. Initial observations showed a lack of enthusiasm and motivation of students in learning Social Studies due to the use of monotonous learning methods. Through the use of Wordwall-based Crossword Puzzle, learning becomes more interactive, interesting, and challenging, so that it can increase student engagement. The results showed a significant increase in learning outcomes; before the use of the media, the majority of students were below 80, while after the implementation, 30 out of 32 students managed to achieve scores above 80. This media not only improves learning outcomes, but also builds students' enthusiasm for learning, creativity, and cooperation in solving learning challenges.